Sodium ion battery and power utilization device
By providing a modified carbon nanotube cladding layer and a fluorocarbon nanotube protective layer on the positive electrode active material layer of the sodium ion battery positive electrode sheet, the problem of insufficient storage time and poor circulation performance when stored in the air is solved, and better storage stability, rate performance and circulation performance are achieved.
Patent Information
- Application Number
- CN202411643876.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing sodium ion battery positive electrode sheets have problems such as insufficient storage time and poor circulation performance when stored in the air, resulting in a degradation of battery performance.
By providing a protective layer on the surface of the positive electrode active material layer away from the current collector side, and using a modified carbon nanotube cladding and fluorocarbon nanotube protective layer in the positive electrode active material layer, the hydrophobicity and carbon dioxide elimination of the electrode sheet are improved, thereby improving the storage capacity and cycling performance of the battery.
This technical method effectively improves the storage stability, rate performance and circulation performance of sodium ion batteries, and reduces the gas production of the battery during storage.
Smart Images

Figure BDA0005139297300000141 
Figure BDA0005139297300000151 
Figure BDA0005139297300000152
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a sodium ion battery and an electrical device. Background Art
[0002] In the field of energy storage, sodium-ion batteries have gradually become a hot topic in research and application due to their advantages such as abundant sodium resources and relatively low cost. However, sodium-ion battery electrodes face an important challenge in practical applications: the high-nickel layered oxides currently used have a large surface area, and the nickel content of the material is relatively high. 3+ Will spontaneously transform into Ni 2+ and release O 2- When the material is exposed to the air, it will react with CO2 and H2O in the air to generate Na2CO3 and NaOH; NaOH will react with the binder PVDF and the electrolyte NaPF6, affecting the battery processing technology and electrochemical performance; the formed Na2CO3 layer will hinder the diffusion of Na. At the same time, since the reaction consumes Na in the material, it will cause capacity decay and poor kinetic performance of the material.
[0003] The above challenges will cause the positive electrode of the sodium-ion battery to fail easily when stored in air, affecting the performance of the subsequent sodium-ion battery. The current way to preserve the electrode in production is to reduce the water content in the air, which greatly increases the production cost and risk. Summary of the invention
[0004] The purpose of the present application is to solve the problems that the existing sodium ion battery positive electrode plates have a short storage time in practical applications and poor cycle performance, and to provide a sodium ion battery and an electrical device with excellent storage performance, rate performance and cycle performance.
[0005] To achieve the above-mentioned objectives, in a first aspect, the present application provides a secondary battery, comprising a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate comprises a positive current collector and a positive active material layer arranged on at least one surface of the positive current collector, and a protective layer is arranged on the surface of the positive active material layer away from the current collector; the positive active material layer comprises a positive active material, the positive active material comprises a layered oxide core, and a coating layer arranged on the outer surface of the layered oxide core, the coating layer comprises modified carbon nanotubes, and the contact angle of the modified carbon nanotubes is ≥90°; the protective layer comprises fluorine-containing carbon nanotubes, and the mass percentage of fluorine element in the fluorine-containing carbon nanotubes is ≥5%.
[0006] As an embodiment of the present application, the contact angle of the modified carbon nanotubes is 90 to 100°.
[0007] As an embodiment of the present application, in the fluorine-containing carbon nanotubes, the mass percentage of fluorine element is 5 to 30%.
[0008] As an implementation scheme of the present application, the positive electrode plate satisfies: 0.5≤M≤8, wherein M=A / B; Anm is the thickness of the coating layer, and B nm is the thickness of the protective layer.
[0009] According to an embodiment of the present application, the thickness A of the coating layer is 50 to 100 nm.
[0010] As an embodiment of the present application, the thickness B of the protective layer is 50 to 100 nm.
[0011] As an embodiment of the present application, the ratio of the thickness of the positive electrode active material layer to the thickness of the protective layer is 1000:(1-2).
[0012] As an embodiment of the present application, the layered oxide core includes Na z Ni x M y O2, wherein 0.1<x≤1, x+y=1, 0.5≤z≤1; and M includes at least one of iron and manganese.
[0013] As an embodiment of the present application, the modified carbon nanotubes include at least one of C12-C18 alkyl groups, C6-C10 aryl groups, C3-C6 perfluoroalkyl groups, C2-C4 ester groups, and C1-C2 halogenated alkyl groups.
[0014] As an embodiment of the present application, the fluorine-containing carbon nanotubes include at least one of C1 to C10 fluoroalkyl groups.
[0015] As an embodiment of the present application, the positive electrode active material layer further includes a conductive agent and a binder.
[0016] As an embodiment of the present application, the conductive agent includes at least one of carbon black, graphite, carbon fiber, carbon nanotube, and graphene.
[0017] As an embodiment of the present application, the binder includes polyvinylidene fluoride.
[0018] In a second aspect of the present application, an electrical device is provided, comprising the above-mentioned sodium ion battery.
[0019] Compared with the prior art, the beneficial effects of this application are:
[0020] The sodium ion battery provided by the present application is provided with a protective layer on the surface of the positive electrode active material layer away from the current collector side, and the protective layer is limited to include carbon nanotubes containing a specific mass percentage of fluorine elements, and the outer surface of the inner core of the layered oxide included in the positive electrode active material layer is coated with modified carbon nanotubes with a specific contact angle range; both can improve the storage capacity of the positive electrode plate in the air on the basis of reducing the impact on the performance of the positive electrode plate, thereby improving the storage capacity of the sodium ion battery and reducing the gas production of the sodium ion battery during storage; and the introduction of the above structure can improve the rate performance and cycle performance of the sodium ion battery. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0022] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0023] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0024] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0025] In one embodiment of the present application, the present application provides a secondary battery, including a positive electrode plate, a negative electrode plate, a separator and an electrolyte, the positive electrode plate including a positive electrode collector and a positive electrode active material layer arranged on at least one surface of the positive electrode collector, and a protective layer is arranged on the surface of the positive electrode active material layer away from the current collector side; the positive electrode active material layer includes a positive electrode active material, the positive electrode active material includes a layered oxide core, and a coating layer arranged on the outer surface of the layered oxide core, the coating layer includes modified carbon nanotubes, and the contact angle of the modified carbon nanotubes is ≥90°; the protective layer includes fluorine-containing carbon nanotubes, and the mass percentage of fluorine element in the fluorine-containing carbon nanotubes is ≥5%.
[0026] The present application has found that by providing a protective layer on the surface of the positive electrode active material layer away from the current collector side, and limiting the protective layer to include carbon nanotubes containing a specific mass percentage of fluorine elements, and the inner core of the layered oxide included in the positive electrode active material layer is coated with modified carbon nanotubes with a specific contact angle range; both can improve the hydrophobicity and carbon dioxide repellency of the positive electrode while reducing the impact on the performance of the positive electrode, thereby improving the storage capacity of the positive electrode in the air, thereby reducing the gas production of the sodium ion battery during the storage process, and improving the storage capacity of the sodium ion battery; and the introduction of the above structure can improve the rate performance and cycle performance of the sodium ion battery.
[0027] Specifically, the modified carbon nanotubes within a specific contact angle range have excellent hydrophobicity on the basis of good electrical conductivity, which can reduce the reaction between the positive electrode and water. The protective layer containing specific substances can effectively reduce the carbon dioxide adsorbed by the coating layer and avoid the influence of carbon dioxide on the positive electrode, thereby reducing the gas production during the storage process of the sodium ion battery. At the same time, the protective layer can also effectively improve the conductivity of the positive electrode, thereby improving the rate performance of the sodium ion battery.
[0028] It should be noted that the test method for the contact angle of the modified carbon nanotube is a nano film contact angle measurement method.
[0029] It should be noted that the modified carbon nanotubes can also be separated from the surface of the positive electrode active material. Since the modified carbon nanotubes are coated on the surface of the positive electrode active material, the modified carbon nanotubes have a strong binding ability with the positive electrode active material. The separation method is: collect the positive electrode sheet, scrape off the protective layer on the surface of the positive electrode sheet, collect the active material in the positive electrode active material layer, place it in NMP, dissolve PVDF in an environment of 40-90°C, repeat 3 times, and collect the remaining powder; place the collected powder in NMP, ultrasonically clean it in a 300W-800W ultrasonic cleaning machine for 2-5 hours, and after cleaning, centrifuge it in a centrifuge at a speed of 5000-8000 rpm for 10-30 minutes, repeat ultrasonication and centrifugation 3-5 times, and vacuum dry the collected sample in a vacuum drying oven at 80-120°C for 10-15 hours, and collect the powder after drying.
[0030] It should be noted that the test principle of the nanofilm contact angle measurement method is as follows: the contact angle refers to the tangent of the gas-liquid interface at the intersection of the gas, liquid and solid phases, and the angle between the tangent on the liquid side and the solid-liquid boundary line. The contact angle of different liquids on different solid surfaces can be tested by the contact angle measuring instrument, so as to study the wettability of different liquids on different solid surfaces, such as spreading, penetration and absorption. Using the sitting drop method, droplets are dropped on the surface of the solid sample, and the image of the shape of the droplets is obtained by the camera, and then a specific mathematical model (such as the droplet can be regarded as a part of a sphere, ellipse or cone) is used to fit and calculate the contact angle through specific parameters (such as width and height). Double-sided tape is pasted on the glass plate around, and the sample is cut into small pieces of about 2cm*8cm in size, and then pasted on the glass plate to make the sample as flat as possible to avoid wrinkles; the syringe is connected to the liquid suction device, and about 10mL of electrolyte is poured into the bottle cap, and the position and height of the sample stage are adjusted. The plastic bottle containing the electrolyte is placed under the needle so that the needle is immersed in the electrolyte. Click the "Control" interface in the software, click "Fill", absorb an appropriate amount of electrolyte about 1 / 3 of the needle tube height, adjust the height of the needle and the sample stage, place the glass plate on the sample stage, press the dropper down to the bottom, and adjust the height of the sample stage so that the bottom of the needle is about 12mm away from the surface of the electrode. Move the sample stage so that the part to be tested is under the needle, and prepare the stopwatch. When it shows "Please drop the liquid on the sample surface", click "Record", immediately press the dropper, and drop the liquid on the needle onto the solid surface.
[0031] It should be noted that the test method for the mass percentage of fluorine in the fluorine-containing carbon nanotubes is surface micro-area element detection. The test principle is: in an analytical instrument such as a scanning electron microscope, when a certain energy and focused electron beam is applied to bombard the sample, the bombarded area will emit characteristic X-rays of the elements contained in the sample. A semiconductor detector is used to convert and amplify the received signal, and then further amplify, process and analyze it through a linear amplifier, a pulse processor, and a multi-channel analyzer. The energy spectrum and intensity value of the characteristic X-rays of each element can be obtained, and then by comparing the X-ray energy spectrum with the standard sample of the corresponding element, and correcting the calculation and processing, the quantitative analysis results of the chemical composition of the sample under test can be obtained. Model: Field emission scanning electron microscope SEM, model Merlin VP Compact; energy spectrometer EDS model XFlash Detector6 / 30. Test method: EDS powder test requires a sample size of about 2g, and the sample size of the electrode and diaphragm is more than 1cm*1cm; all samples must be ensured to be dry and free of colloidal and liquid substances; samples removed from the battery must be dried before being sent for testing; create EDS files: open the EDS test software and enter the relevant information of the test sample according to the navigation map; based on the actual situation of the sample, use reconstruction and peak-only methods to confirm the elements of the sample; after confirmation, select the peak calibration editor to remove redundant element identifiers; the spectrum shows the position and height of the X-ray characteristic peaks of the tested elements; the test sample area contains the normalized weight percentage and atomic percentage of the elements.
[0032] Exemplarily, the contact angle of the modified carbon nanotubes can be any point value ≥90° or any two point range values, such as 90-100°, 90-110°, 90-120°, 90-160°, or can be one of 90°, 100°, 110°, 120°, 130°, 140°, 150°, 160° or any two range values.
[0033] Exemplarily, in the fluorine-containing carbon nanotubes, the mass percentage of fluorine element can be any point value ≥5% or any two point range values, for example, it can be 5-30%, 5-20%, 5-50%, etc., or it can be one of 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or any two range values.
[0034] In one embodiment, the contact angle of the modified carbon nanotubes is 90-100°.
[0035] The present application has found that the contact angle of the modified carbon nanotubes can reflect the hydrophobicity of the modified carbon nanotubes to a certain extent. The present application has found that when the contact angle of the modified carbon nanotubes is further selected to be 90-100°, on the basis of not affecting the electrochemical properties of the positive electrode plate, not only the hydrophobicity of the obtained positive electrode plate is better, but also the interaction between it and carbon dioxide is weakened, thereby being able to simultaneously achieve good hydrophobicity and carbon dioxide repellency, thereby improving the storage stability of the positive electrode plate, thereby improving the storage stability of the sodium ion battery, and reducing the gas production of the sodium ion battery during storage; at the same time, it can also improve the cycle performance of the sodium ion battery.
[0036] Exemplarily, the contact angle of the modified carbon nanotubes can be any point value between 90 and 100° or any two point range values, for example, it can be one of 90°, 91°, 92°, 93°, 94°, 95°, 96°, 97°, 98°, 99°, 100° or any two range values.
[0037] In one embodiment, the contact angle of the modified carbon nanotubes is 93-96°.
[0038] In one embodiment, the mass percentage of fluorine element in the fluorine-containing carbon nanotubes is 5-30%.
[0039] The present application study found that the mass percentage of fluorine in fluorine-containing carbon nanotubes will affect the electronegativity of the fluorine-containing carbon nanotubes, thereby affecting not only the blocking effect of the fluorine-containing carbon nanotubes on the entry of carbon dioxide, but also the conductive effect; when the mass percentage of fluorine in the fluorine-containing carbon nanotubes is further selected to be 5 to 30%, the storage stability of the obtained positive electrode plate is better, the storage stability of the corresponding sodium-ion battery is also better, and the rate performance is also better.
[0040] In one embodiment, the mass percentage of fluorine element in the fluorine-containing carbon nanotubes is 10-20%.
[0041] In one embodiment, the positive electrode plate satisfies: 0.5≤M≤8, wherein M=A / B; Anm is the thickness of the coating layer, and B nm is the thickness of the protective layer.
[0042] It should be noted that the thickness of the coating layer is tested by FIB focused ion beam technology; the thickness of the protective layer is tested by scanning electron microscope (Zeiss, model: Merlin VP Compact) after polishing by argon ion polisher (JEOL, model: IB-19520CCP).
[0043] Exemplarily, the M may be any point value or any two point range values between 0.5-8, for example, it may be one of 0.5, 1, 2, 3, 4, 5, 6, 7, 8 or any two range values.
[0044] The present application has found that when the ratio M of the thickness of the coating layer to the thickness of the protective layer is within the range given in the present application, it can ensure that carbon dioxide does not enter the positive electrode sheet and can also prevent carbon dioxide molecules from aggregating, thereby improving the storage performance of the positive electrode sheet and reducing the storage gas production of the corresponding sodium ion battery; at the same time, M can also provide a suitable distance for ion diffusion within the above range, ensuring the high conductivity of the positive electrode sheet, thereby ensuring the excellent rate performance of the sodium ion battery.
[0045] In one embodiment, the positive electrode sheet satisfies: 1≤M≤5. For example, M can be a range of one or any two of 1, 1.3, 1.5, 1.8, 2, 2.3, 2.5, 2.8, 3, 3.3, 3.5, 3.8, 4, 4.3, 4.5, 4.8, and 5. The present application has found that when M is further selected to be 1 to 5, the overall performance of the obtained sodium ion battery is better.
[0046] In one embodiment, the thickness A of the coating layer is 50-100 nm.
[0047] Exemplarily, the thickness A of the coating layer can be any point value or any two point range values between 50 and 100 nm, for example, it can be one or any two range values of 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, and 100 nm.
[0048] The present application has found that the coating layer in the range of 50 to 100 nm can achieve a good balance between conductivity and hydrophobicity and carbon dioxide repellency, achieving an excellent overall effect; specifically, on the one hand, the coating layer in the above thickness range can avoid the problem of poor electrical contact due to too small thickness of the coating layer, thereby reducing the rate performance of the sodium ion battery, and can also avoid the problem of weak hydrophobicity and carbon dioxide repellent effect due to too small thickness, thereby affecting the storage performance of the positive electrode sheet and the sodium ion battery; on the other hand, within the above thickness range, it can also avoid the problem of increased migration distance between ions and the positive electrode active material due to too large thickness of the coating layer, thereby affecting the ion transmission efficiency, and further affecting the rate performance of the sodium ion battery.
[0049] In one embodiment, the thickness B of the protective layer is 50-100 nm.
[0050] Exemplarily, the thickness A of the protective layer can be any point value or any two point range values between 50 and 100 nm, for example, it can be one or any two range values of 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, and 100 nm.
[0051] The present application study found that when the thickness of the protective layer is 50 to 100 nm, it can effectively prevent carbon dioxide from entering the positive electrode plate while avoiding a significant increase in the ion diffusion distance that affects the rate performance of the sodium ion battery.
[0052] In one embodiment, the ratio of the thickness of the positive electrode active material layer to the thickness of the protective layer is 1000:(1-2).
[0053] It should be noted that the ratio of the thickness of the positive electrode active material layer to the thickness of the protective layer is a dimensioned ratio, and the thickness of the positive electrode active material layer is obtained by polishing with an argon ion polisher (JEOL, model: IB-19520CCP) and then tested with a scanning electron microscope (Zeiss, model: Merlin VP Compact). Exemplarily, the ratio of the thickness of the positive electrode active material layer to the thickness of the protective layer can be any point value or any two point range values between 1000: (1 to 2), such as 1000: 1, 1000: 1.2, 1000: 1.4, 1000: 1.6, 1000: 1.8, 1000: 2, or any two range values.
[0054] This application study found that an important mechanism for carbon dioxide barrier is achieved through steric hindrance. The thicker the positive electrode sheet, the stronger its adsorption capacity for carbon dioxide in the air, and the thinner it is, the weaker its adsorption capacity. The ratio of the thickness of the positive electrode active material layer to the thickness of the protective layer in the range of 1000: (1-2) can achieve a good and suitable ion transmission path while achieving a barrier effect on water and carbon dioxide, thereby improving the storage performance of the positive electrode sheet, reducing the storage gas production of the sodium ion battery, and improving the cycle performance and rate performance of the sodium ion battery.
[0055] In one embodiment, the thickness of the positive electrode active material layer is 50-130 μm.
[0056] Exemplarily, the thickness of the positive electrode active material layer may be any point value or any two point range values between 50 and 130 μm, for example, it may be one of 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm or any two range values.
[0057] The present application study found that a positive electrode active material layer within a suitable thickness range can achieve better cycle performance and rate performance of sodium ion batteries.
[0058] In one embodiment, the layered oxide core comprises Na z Ni x M yO2, wherein 0.1<x≤1, x+y=1, 0.5≤z≤1; and M includes at least one of iron and manganese.
[0059] In one embodiment, the layered oxide core comprises Na 2 / 3 Ni 1 / 3 Mn 2 / 3 O2、NaNi 1 / 2 Mn 1 / 2 O2、Na 0.67 Ni 0.33 Mn 0.67 O2、Na 1.1 Mn 0.45 Ni 0.45 O2、NaNi 1 / 2 Fe 1 / 2 O2、NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2、NaNi 2 / 5 Fe 1 / 10 Mn 1 / At least one of 2O2.
[0060] In one embodiment, 0.6<x≤1.
[0061] The present application study found that when the layered oxide core is further selected to include the above-mentioned substances, the overall performance of the resulting sodium ion battery is better.
[0062] In one embodiment, the modified carbon nanotubes include at least one of C12-C18 alkyl groups, C6-C10 aryl groups, C3-C6 perfluoroalkyl groups, C2-C4 ester groups, and C1-C2 halogenated alkyl groups.
[0063] It should be noted that the test method for the groups in the modified carbon nanotubes is: scrape the surface of the positive electrode plate and collect the positive electrode active material layer material in the positive electrode plate, and then characterize the modified functional groups in the coating layer by Raman testing.
[0064] The present application has found that when the above groups are included in the modified carbon nanotubes, the contact angle of the modified carbon nanotubes can be within the range given in the present application.
[0065] In one embodiment, the modified carbon nanotubes include C3-C6 perfluoroalkyl groups.
[0066] The present application study found that fluorine atoms have a strong electronegativity. When further selecting to modify carbon nanotubes including C3-C6 perfluoroalkyl groups, that is, when C3-C6 perfluoroalkyl groups are used for modification, the carbon-fluorine bond in the C3-C6 perfluoroalkyl group has a strong polarity and the fluorine atom has a large electronegativity, which makes the electron cloud of the carbon-fluorine bond strongly biased toward the fluorine atom, resulting in the perfluoroalkyl group having a lower surface energy. In the range of 3 to 6 carbon atoms, this carbon-fluorine structure can effectively repel water molecules and show good hydrophobicity. The shorter carbon chain length makes the arrangement of the perfluoroalkyl group on the surface of the material more compact, further enhancing the hydrophobic effect. In addition, from the perspective of the surface microstructure, the perfluoroalkyl group in this range of carbon atoms can form a relatively dense and delicate micro-convex structure after modifying the surface of the carbon nanotube. This microstructure can increase the roughness of the surface of the modified carbon nanotube. According to the Cassie-Baxter theory, the rough surface structure can enhance the hydrophobicity of the material, increase the contact angle of water droplets on the surface of the material, and thus achieve a better hydrophobic effect. This can improve the storage stability of the positive electrode, reduce gas production during the storage process of the sodium-ion battery, and improve the rate performance and cycle performance of the sodium-ion battery.
[0067] In one embodiment, the modified carbon nanotubes can be purchased from the market or can be prepared by ourselves.
[0068] In one embodiment, the preparation method of the modified carbon nanotubes can be an ultrasound-assisted method, in which the carbon nanotubes, the modifier containing the corresponding functional groups and the solvent are placed in a reaction container, and ultrasonic treatment is performed in an ultrasonic cleaner, and the cavitation effect and mechanical stirring effect of ultrasound are used to promote the reaction, and then the product is collected by centrifugation.
[0069] The contact angle of the modified carbon nanotubes in the present invention can be achieved by adjusting the reaction mass ratio of the modifier and the carbon nanotubes or the type of the modifier.
[0070] In one embodiment, the fluorine-containing carbon nanotubes include at least one of C1-C10 fluoroalkyl groups.
[0071] It should be noted that the test method for the groups in the fluorine-containing carbon nanotubes is: scrape the surface of the positive electrode plate and collect the protective layer material in the positive electrode plate, and then characterize the modified functional groups in the protective layer by Raman testing.
[0072] In one embodiment, the fluorinated carbon nanotubes include perfluorooctyl (-C8F 17 ) and perfluorohexyl (-C6F 13 ).
[0073] The present application has found that when further selecting fluorinated carbon nanotubes including perfluorooctyl (-C8F 17 ) and perfluorohexyl (-C6F 13) when the obtained fluorinated carbon nanotubes have a relatively better carbon dioxide repelling effect; on the one hand, the fluorine atom content of perfluorooctyl and perfluorohexyl is high, and the fluorine atom has a strong electronegativity. The presence of a large number of fluorine atoms causes a significant change in the electron distribution of the molecule, resulting in a weakened interaction between the fluorinated carbon nanotubes and the carbon dioxide molecules. On the other hand, the carbon chain length of perfluorooctyl and perfluorohexyl is moderate, which can provide sufficient steric hindrance to prevent carbon dioxide molecules from approaching and interacting; thereby improving the storage performance, rate performance and cycle performance of sodium ion batteries.
[0074] In one embodiment, the fluorine-containing carbon nanotubes can be purchased from the market, or can be made by oneself.
[0075] In one embodiment, the preparation method of the fluorine-containing carbon nanotubes can be an ultrasound-assisted method, in which the carbon nanotubes, a modifier containing corresponding functional groups, and a solvent are placed in a reaction container, and ultrasonic treatment is performed in an ultrasonic cleaner, and the cavitation effect and mechanical stirring effect of ultrasound are used to promote the reaction, and then the product is collected by centrifugation.
[0076] In one embodiment, the positive electrode active material layer further includes a conductive agent and a binder.
[0077] In one embodiment, the conductive agent includes at least one of carbon black, graphite, carbon fiber, carbon nanotube, and graphene.
[0078] In one embodiment, the binder includes polyvinylidene fluoride.
[0079] In one embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector; the negative electrode active material layer includes a negative electrode active material. The present application has no limitation on the negative electrode active material, and any known negative electrode active material can be used.
[0080] In one embodiment, the electrolyte includes an organic solvent, a sodium salt and an additive. The present application has no limitation on the organic solvent, sodium salt and additive in the electrolyte, and any known organic solvent, sodium salt and additive can be used.
[0081] Illustratively, the organic solvent includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, and dimethyl carbonate; the sodium salt includes at least one of sodium perchlorate and sodium hexafluorophosphate; and the additive includes at least one of a film-forming additive, a conductive additive, and a flame retardant additive.
[0082] In one embodiment, the separator of the secondary battery is disposed between the positive electrode and the negative electrode.
[0083] In one embodiment of the present application, the present application proposes an electrical device, and the electrical device includes the secondary battery described in the present application.
[0084] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0085] Example 1
[0086] The present invention provides a secondary battery, wherein a method for preparing the secondary battery comprises the following steps:
[0087] (1) Preparation of positive electrode sheet
[0088] 1) Preparation of modified carbon nanotubes:
[0089] S1. Pretreatment of carbon nanotubes: weigh a certain amount of original carbon nanotubes, put them into a crucible, calcine them at 400°C for 2 hours in a muffle furnace, cool them to room temperature after calcination, then add the carbon nanotubes into concentrated nitric acid, reflux them at 80°C for 6 hours, filter them after reflux treatment, repeatedly rinse the filter residue with deionized water until it is neutral, and then dry them in a vacuum drying oven at 80°C for 12 hours to obtain pretreated carbon nanotubes for later use;
[0090] S2, modification reaction: accurately weigh 0.5g of the pretreated carbon nanotubes and add them to 100mL of ethanol, and ultrasonically disperse them for 30 minutes to form a uniform suspension. Add 12g of perfluorooctylpropyl alcohol to the above suspension. Place the mixed solution in an ultrasonic cleaner and ultrasonically treat it at 40°C for 4 hours;
[0091] S3, product separation and purification: After the ultrasonic treatment in step S2, the reaction solution was centrifuged at 8000 rpm for 15 minutes, and the supernatant was removed. The precipitate was repeatedly washed with ethanol for 3 times, and finally the washed precipitate was dried in a vacuum drying oven at 80°C for 12 hours to obtain perfluorooctyl-modified carbon nanotubes, and the contact angle of the obtained modified carbon nanotubes was 95°;
[0092] 2) Preparation of fluorinated carbon nanotubes:
[0093] S1. Pretreatment of carbon nanotubes: weigh an appropriate amount of raw carbon nanotubes, put them into a crucible, calcine them in a muffle furnace at 500°C for 2.5 hours, cool them to room temperature after calcination, then add the carbon nanotubes into concentrated nitric acid, reflux them at 85°C for 5 hours, filter them after reflux treatment, repeatedly rinse the filter residue with deionized water until it is neutral, and then dry them in a vacuum drying oven at 70°C for 11 hours to obtain pretreated carbon nanotubes for standby use;
[0094] S2, modification reaction: accurately weigh 20g of pretreated carbon nanotubes, add them to 200mL of ethanol, and use an ultrasonic cleaner to ultrasonically disperse for 25 minutes to form a uniform suspension. Add 15g of zinc perfluorooctanoate to the above suspension. Place the mixed solution in an ultrasonic cleaner and ultrasonically treat it at 40°C for 4 hours;
[0095] S3, product separation and purification: After the ultrasonic treatment in step S2, the reaction solution was centrifuged at 7000 rpm for 12 minutes, the precipitate was collected and washed repeatedly with ethanol for 3 times, and finally the washed precipitate was dried in a vacuum drying oven at 70°C for 10 hours to obtain perfluorozinc-modified carbon nanotubes. The mass percentage of fluorine in the obtained fluorine-containing carbon nanotubes was 20%;
[0096] 3) Preparation of positive electrode active materials: Na 2 / 3 Ni 1 / 3 Mn 2 / 3 O2 was used as the core of the positive electrode active material. The positive electrode material and the modified carbon nanotubes were ball milled in a planetary ball mill at a mass ratio of 10:1 at a speed of 400 rpm for 6 hours to obtain a positive electrode active material with a coating layer thickness of 60 nm.
[0097] 4) The positive electrode active material, conductive agent (Suepr P) and binder (PVDF) prepared in step 3) are mixed in NMP at a mass ratio of 96:1.5:2.5. After the mixing is completed, the slurry is evenly coated on the aluminum foil current collector and dried to obtain a positive electrode active material layer. The thickness of the positive electrode active material layer is 60 μm; then the fluorinated carbon nanotubes prepared in step 2) and PVDF are mixed in NMP solution at a mass ratio of 97:3. After the mixing is completed, they are evenly applied to one side of the dried electrode sheet and dried to obtain a protective layer. The thickness of the protective layer is 60 nm;
[0098] (2) Preparation of negative electrode sheet
[0099] The hard carbon negative electrode material, the conductive agent acetylene black (Super P), the thickener (CMC) and the binder (SBR) are mixed uniformly in a mass ratio of 93:3:2:2, the mixed slurry is coated on the copper foil current collector, and dried to obtain a negative electrode sheet;
[0100] (3) Preparation of electrolyte
[0101] Select sodium hexafluorophosphate as the sodium salt, prepare a solvent (a mixed solvent formed by mixing ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1), and the additive is 3% fluoroethylene carbonate. The concentration of sodium hexafluorophosphate is 1 mol / L. Slowly add the weighed sodium hexafluorophosphate to the mixed solvent and stir to fully dissolve it for 2 hours. Then add 3% fluoroethylene carbonate in the total volume of the solvent and continue stirring for 30 minutes to obtain an electrolyte;
[0102] (4) Preparation of sodium ion batteries
[0103] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets. A bare battery cell is obtained by winding, hot pressing, and welding the tabs. The bare battery cell is placed in an outer packaging aluminum-plastic film and baked in an oven at 85±10°C for 24 hours. The prepared negative electrode material is injected into the dried battery, allowed to stand, formed, and divided to complete the preparation of the sodium ion soft-pack battery.
[0104] Embodiments 2 to 4
[0105] The embodiment of the present application provides a sodium ion battery. The difference between the preparation method of the sodium ion battery and that of Example 1 is that the preparation process of the modified carbon nanotubes is adjusted to achieve the parameters in Table 1.
[0106] Embodiments 5 to 8
[0107] The embodiment of the present application provides a sodium ion battery. The difference between the preparation method of the sodium ion battery and that of Example 1 is that the preparation process of the fluorine-containing carbon nanotubes is adjusted to achieve the parameters in Table 1.
[0108] Embodiments 9 to 15
[0109] The embodiment of the present application provides a sodium ion battery. The difference between the preparation method of the sodium ion battery and that of Example 1 is that the thickness of the coating layer and the thickness of the protective layer in the preparation of the positive electrode active material are adjusted to achieve the parameters in Table 1.
[0110] Example 16
[0111] The embodiment of the present application provides a sodium ion battery. The difference between the preparation method of the sodium ion battery and that of Example 1 is that the thickness of the positive electrode active material layer is adjusted to achieve the parameters in Table 1.
[0112] Embodiment 17
[0113] The embodiment of the present application provides a sodium ion battery. The difference between the preparation method of the sodium ion battery and that of Example 1 is that the core of the positive electrode active material is adjusted to achieve the parameters in Table 1.
[0114] Embodiment 18
[0115] The embodiment of the present application provides a sodium ion battery. The difference between the preparation method of the sodium ion battery and that of Example 1 is that the preparation of the modified carbon nanotubes is adjusted to achieve the parameters in Table 1.
[0116] Embodiment 19
[0117] The embodiment of the present application provides a sodium ion battery. The difference between the preparation method of the sodium ion battery and that of Example 1 is that the preparation of the fluorine-containing carbon nanotubes is adjusted to achieve the parameters in Table 1.
[0118] Embodiment 20
[0119] The embodiment of the present application provides a sodium ion battery. The difference between the preparation method of the sodium ion battery and that of Example 1 is that the preparation of the fluorine-containing carbon nanotubes is adjusted to achieve the parameters in Table 1.
[0120] Embodiment 21
[0121] The embodiment of the present application provides a sodium ion battery. The difference between the preparation method of the sodium ion battery and that of Example 1 is that the preparation of the fluorine-containing carbon nanotubes is adjusted to achieve the parameters in Table 1.
[0122] Comparative Example 1
[0123] The comparative example of the present application provides a sodium ion battery. The difference between the preparation method of the sodium ion battery and that of Example 1 lies in that the preparation process of the modified carbon nanotubes is adjusted to achieve the parameters in Table 1.
[0124] Comparative Example 2
[0125] The comparative example of the present application provides a sodium ion battery. The difference between the preparation method of the sodium ion battery and that of Example 1 lies in that the preparation process of the fluorine-containing carbon nanotubes is adjusted to achieve the parameters in Table 1.
[0126] Comparative Example 3
[0127] The comparative example of the present application provides a sodium ion battery, and the preparation method of the sodium ion battery is different from that of Example 1 in that no coating layer is provided.
[0128] Comparative Example 4
[0129] The comparative example of the present application provides a sodium ion battery, and the preparation method of the sodium ion battery is different from that of Example 1 in that no protective layer is provided.
[0130] The contact angle and modified groups of the modified carbon nanotubes in the coating layer, the mass percentage of fluorine elements and modified groups in the fluorine-containing carbon nanotubes in the protective layer, the thickness A of the coating layer, the thickness B of the protective layer, the value M of A / B, the ratio N of the thickness of the positive electrode active material layer to the thickness of the protective layer, and the layered oxide core in the embodiments and comparative examples are shown in Table 1;
[0131] Table 1 Parameters of sodium ion batteries
[0132]
[0133]
[0134] The performance tests of the sodium ion batteries prepared in the examples and comparative examples include the following aspects:
[0135] (1) Storage stability: At 25°C, the soft-pack batteries obtained in each embodiment and comparative example were charged to 3.95V at a charge rate of 0.33C, left for 5 minutes, and then discharged to 1.5V at a discharge rate of 0.33C, repeated three times, and then charged at a charge rate of 0.33C for 90 minutes and adjusted to 50% SOC. At 50% SOC, the pressure after 30 days of storage was tested, in KPa, and recorded in Table 2;
[0136] (2) Rate performance: At 25° C., the soft-pack batteries obtained in each embodiment and comparative example were charged to 3.95 V at a charge rate of 0.33 C, left for 5 minutes, and then discharged to 1.5 V at a discharge rate of 0.33 C. This was repeated three times to obtain an average value; the soft-pack batteries were then charged to 3.95 V at a charge rate of 0.33 C, left for 5 minutes, and then discharged to 1.5 V at a discharge rate of 5 C. This was repeated three times to obtain an average value. The capacity retention rate at a rate of 5 C was obtained and recorded in Table 2.
[0137] (3) Cycle performance: The soft-pack batteries obtained in each embodiment and comparative example were charged to 3.95 V at a charge rate of 1 C, left for 5 minutes, and then discharged to 1.5 V at a discharge rate of 1 C, and cycled 1000 times; the capacity retention rate after 1000 cycles was obtained and recorded in Table 2.
[0138] Table 2 Performance test results of sodium ion batteries
[0139]
[0140]
[0141] It can be seen from Table 2 that when the technical solution provided by the present application is adopted, the obtained sodium ion battery has excellent storage stability, rate performance and cycle performance; specifically, the pressure of the obtained sodium ion battery after storage for 30 days at 50% SOC is below 0.22 KPa, the capacity retention rate at 5C rate is above 85%, and the capacity retention rate after 1000 cycles is above 81%;
[0142] It can be seen from Examples 1 to 18 and Comparative Example 1 that when the contact angle of the modified carbon nanotubes used in the positive electrode active material coating layer is not within the range given in the present application, the storage stability of the obtained sodium ion battery deteriorates significantly. The main reason is that when the contact angle is not within the range, the positive electrode active material is hydrophilic and will absorb more moisture in the air, and the increase in moisture will lead to an increase in gas production; It can be seen from Examples 1 to 18 and Comparative Example 2 that when the mass percentage of fluorine in the fluorine-containing carbon nanotubes used in the protective layer is not within the range given in the present application, the storage stability of the obtained sodium ion battery deteriorates significantly. The main reason is that when the fluorine content in the fluorine-containing carbon nanotubes is not within the application range, the ability of the perfluoroalkyl group to isolate CO2 is weakened, and CO2 will react with the material to generate CO3 2- , which will lead to more gas production, thereby affecting the electrochemical performance of the sodium ion battery; it can be seen from Examples 1 to 18 and Comparative Example 3 that when the positive electrode active material is not introduced into the coating layer, the storage stability, rate performance and cycle performance of the obtained sodium ion battery will be significantly deteriorated. The main reason is that the coating layer plays a role in improving the electronic conductivity of the material and enhancing the hydrophobicity of the material. The electronic conductivity is strongly correlated with the cycle and rate performance of the material, while the hydrophobicity is strongly correlated with the storage stability of the material. When the coating layer is not introduced, the electronic conductivity and hydrophobicity of the material will be significantly deteriorated. Therefore, the storage stability, rate performance and cycle performance of the sodium ion battery are all reduced; it can be seen from Examples 1 to 18 and Comparative Example 4 that when the protective layer is not introduced, the storage stability of the obtained sodium ion battery is significantly deteriorated. The main reason is that the main function of the protective layer is to isolate CO2 in the air and alleviate the generation of CO3 by the material 2- , so as to achieve the purpose of suppressing gas production. Therefore, the elimination of the protective layer will cause more CO3 to be generated on the surface of the positive electrode active material. 2- , thus deteriorating storage performance.
[0143] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The positive electrode sheet comprises a positive current collector and a positive active material layer arranged on at least one surface of the positive current collector, and a protective layer is arranged on the surface of the positive active material layer away from the current collector; The positive electrode active material layer comprises a positive electrode active material, the positive electrode active material comprises a layered oxide core, and a coating layer arranged on the outer surface of the layered oxide core, the coating layer comprises modified carbon nanotubes, and the contact angle of the modified carbon nanotubes is ≥90°; The protective layer comprises fluorine-containing carbon nanotubes, and the mass percentage of fluorine element in the fluorine-containing carbon nanotubes is ≥5%.
2. The sodium ion battery according to claim 1, characterized in that The contact angle of the modified carbon nanotubes is 90 to 100°; And / or, in the fluorine-containing carbon nanotubes, the mass percentage of fluorine element is 5-30%.
3. The sodium ion battery according to claim 1, characterized in that: The positive electrode sheet satisfies: 0.5≤M≤8, Where, M = A / B; Anm is the thickness of the coating layer, B nm is the thickness of the protective layer.
4. The sodium ion battery according to claim 1, characterized in that Satisfy at least one of the following: a. The thickness A of the coating layer is 50 to 100 nm; b. The thickness B of the protective layer is 50 to 100 nm.
5. The sodium ion battery according to claim 1, characterized in that: The ratio of the thickness of the positive electrode active material layer to the thickness of the protective layer is 1000:(1-2).
6. The sodium ion battery according to claim 1, characterized in that: The layered oxide core includes Na z Ni x M y O2, Among them, 0.1<x≤1, x+y=1, 0.5≤z≤1; M includes at least one of iron and manganese.
7. The sodium ion battery according to claim 1, characterized in that: The modified carbon nanotubes include at least one of C12-C18 alkyl, C6-C10 aryl, C3-C6 perfluoroalkyl, C2-C4 ester, and C1-C2 halogenated alkyl.
8. The sodium ion battery according to claim 1, characterized in that: The fluorine-containing carbon nanotubes include at least one of C1-C10 fluoroalkyl groups.
9. The sodium ion battery according to claim 1, characterized in that: The positive electrode active material layer also includes a conductive agent and a binder; And / or, the conductive agent includes at least one of carbon black, graphite, carbon fiber, carbon nanotube, and graphene; And / or, the binder includes polyvinylidene fluoride.
10. An electrical device, characterized in that: It comprises the sodium ion battery as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Electrochemical device and electronic device
CN114551789A
Hydrophobic sodium ion battery positive electrode material, preparation method thereof and sodium ion battery
CN115911319A